An Investigation on How Entrepreneurial Orientation Determines SMEs Survival - Sulhaini Sulhaini; Baiq Handayani Rinuastuti; Siti Nurmayanti (Faculty of Economics, Universitas Sriwijaya, 2023)
This study aims to fill some fundamental research gaps by examining a model of the chain effect of entrepreneurial orientation (EO) on a firm's ability to survive during a pandemic. With the help of research assistants, the team collected data from five districts in the Lombok Island, Indonesia. Data were collected from purposively selected small and medium-sized enterprises (SMEs) that were established before the pandemic and were able to get through it. The findings provided some interesting understandings. First, EO does not directly strengthen knowledge assets (KAs). However, in difficult situations, EO becomes the foundation for redirecting and redesigning internal human resource practices (IHRPs) and relational capability (RC) to strengthen KAs and ensure firm survival. Second, EO prevents firms from failing by being proactive and innovative risk takers in reformulating and energizing internal practices and capabilities to strengthen KAs and survival. Third, survival requires innovativeness, proactiveness and risk taking behavior to quickly and efficiently redesign strategy, capability and assets.